Reconceptualizing Financial Freedom through Maqāṣid al-Sharīʿah fi Ḥifẓ al-Māl as a Framework for Sustainable Economic Development - Ubaidillah; Dede Nurohman; Ahmad Muhtadi Anshor (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
Global economic instability and the increasing complexity of personal financial management demand a more ethical, stable, and sustainable approach. In this context, Islamic economic practitioners propose various innovations to revitalize financial freedom based on the principles of Maqāṣid al-Sharīʿah, particularly Ḥifẓ al-Māl. This study aims to analyze the integration of the Ḥifẓ al-Māl principle into financial planning and management and its contribution to improving the financial Wellbeing of individuals and society. The research employs a qualitative case study design, supported by descriptive analysis. Data were obtained from reputable scientific journals, official reports from international institutions, and in-depth interviews with Islamic economics experts and Islamic finance practitioners. Furthermore, statistical data related to financial stability and Islamic investment behavior were used to strengthen the findings. The results show that the application of Islamic principles, particularly the avoidance of gharar, proportional risk management, and commitment to the public interest, contributes to improving individual financial stability by decreasing the risk of default and increasing the accumulation of productive assets. The integration of Hifdz al-Mal also encourages safer, more inclusive, and long-term investment practices, thereby strengthening public trust in the Islamic financial system. This study concludes that consistent implementation of Maqasid al-Shariah can be an effective strategy for building equitable and sustainable financial freedom. The implications of these findings are relevant for individuals, financial institutions, and policymakers in designing financial instruments and programs that respond to the dynamics of the modern economy.